LVP keratoprosthesis: anatomical and functional outcomes in bilateral end-stage corneal blindness. Issue 5 (11th June 2018) - Basu, Sayan; Nagpal, Ritu; Serna-Ojeda, Juan Carlos; Bhalekar, Swapnil; Bagga, Bhupesh; Sangwan, Virender
Abstract : Purpose: To describe the anatomical and functional outcomes of the novel LVP keratoprosthesis (Kpro), developed as an alternative to the modified osteo-odonto keratoprosthesis (MOOKP), in eyes with end-stage corneal blindness where conventional corneal surgeries are contraindicated. Methods: This prospective case series included 58 eyes of 56 patients (12 children and 44 adults) with severe bilateral keratopathy and completely dry, dermalised ocular surfaces who underwent unilateral LVP Kpro implantation from 2012 to 2016. In this two-stage procedure, an ocular surface labial mucous membrane grafting was performed, followed for 3 months by the implantation of the device under the engrafted mucosal flap. The primary outcome measures were anatomical retention rate and improvement in best corrected visual acuity (BCVA). The secondary outcome measure was rate of occurrence of complications. Results: Mean postoperative follow-up was 2.5±1.1 years. Kaplan-Meier survival analysis showed an anatomical retention rate of 90.8%±3.9% at 1 year, 80%±5.7% at 2 years and 76.6%±6.5% at 3–5 years. The survival rates were comparable in children and adults (91% vs 72% at 5 years, p=0.258). About 61.5% of eyes maintained 20/400 or better vision and median BCVA improved from perception of light to 20/70 at 1 year postoperatively (p<0.0001). Complications like retroprosthetic membrane formation, glaucoma, vitritis, endophthalmitis and panophthalmitis occurred in 43%, 26%, 22%, 12% and 3% of the eyes, respectively. Conclusion: The LVP Kpro is an effective procedure for the treatment of end-stage corneal blindness in completely dry eyes. The LVP Kpro can be particularly useful in situations where the MOOKP is contraindicated or difficult to perform.